Effect of Algal Inoculation on COD and Nitrogen Removal, and Indigenous Bacterial Dynamics in Municipal Wastewater - Lee, Jangho; Lee, Jaejin; Shukla, Sudheer Kumar; Park, Joonhong; Lee, Tae Kwon (Journal of microbiology and biotechnology, 2016)
The effects of algal inoculation on chemical oxygen demand (COD) and total nitrogen (TN) removal, and indigenous bacterial dynamics were investigated in municipal wastewater. Experiments were conducted with municipal wastewater inoculated with either Chlorella vulgaris AG10032, Selenastrum gracile UTEX 325, or Scenedesmus quadricauda AG 10308. C. vulgaris and S. gracile as fast growing algae in municipal wastewater, performed high COD and TN removal in contrast to Sc. quadricauda. The indigenous bacterial dynamics revealed by 16S rRNA gene amplification showed different bacterial shifts in response to different algal inoculations. The dominant bacterial genera of either algal case were characterized as heterotrophic nitrifying bacteria. Our results suggest that selection of indigenous bacteria that symbiotically interact with algal species is important for better performance of wastewater treatment.